Binding to E1 and E3 is mutually exclusive for the human autophagy E2 Atg3. (23rd October 2013) - Qiu, Yu; Hofmann, Kay; Coats, Julie E.; Schulman, Brenda A.; Kaiser, Stephen E.
Abstract: Ubiquitin‐like proteins (UBLs) are activated, transferred and conjugated by E1‐E2‐E3 enzyme cascades. E2 enzymes for canonical UBLs such as ubiquitin, SUMO, and NEDD8 typically use common surfaces to bind to E1 and E3 enzymes. Thus, canonical E2s are required to disengage from E1 prior to E3‐mediated UBL ligation. However, E1, E2, and E3 enzymes in the autophagy pathway are structurally and functionally distinct from canonical enzymes, and it has not been possible to predict whether autophagy UBL cascades are organized according to the same principles. Here, we address this question for the pathway mediating lipidation of the human autophagy UBL, LC3. We utilized bioinformatic and experimental approaches to identify a distinctive region in the autophagy E2, Atg3, that binds to the autophagy E3, Atg12∼Atg5‐Atg16. Short peptides corresponding to this Atg3 sequence inhibit LC3 lipidation in vitro . Notably, the E3‐binding site on Atg3 overlaps with the binding site for the E1, Atg7. Accordingly, the E3 competes with Atg7 for binding to Atg3, implying that Atg3 likely cycles back and forth between binding to Atg7 for loading with the UBL LC3 and binding to E3 to promote LC3 lipidation. The results show that common organizational principles underlie canonical and noncanonical UBL transfer cascades, but are established through distinct structural features.